Importance of Evaluating D-Dimer, CRP, LDH, and RBS as Predictors in the Severity of COVID-19 Disease: Omicron Variant - Alrubayei , Zainab Mohsin Ali; Naser, Israa Habeeb; Jawad, Noor Muhsin; Jameel, Zahraa Isam (Medical Science Journal for Advance Research, 2026)
Background: COVID-19 is associated with systemic inflammation, coagulation abnormalities, and metabolic disturbances that contribute to disease severity. Biomarkers such as D-dimer, C-reactive protein (CRP), and lactate dehydrogenase (LDH) have been identified as potential severity predictors, yet their combined diagnostic value and the influence of demographic factors remain incompletely characterized. Objective: To evaluate inflammatory, coagulation, and metabolic biomarkers in patients with moderate-to-severe COVID-19 and assess the influence of age and gender on these parameters. Methods: This cross-sectional study enrolled 260 hospitalized COVID-19 patients confirmed by quantitative reverse transcription polymerase chain reaction (RT-qPCR) and 50 healthy controls. Serum and plasma levels of D-dimer, CRP, LDH, and random blood sugar (RBS) were measured using fully automated apparatus methods. Statistical analysis included t-tests and analysis of variance to compare parameters across groups and demographic strata. Results: COVID-19 patients demonstrated significantly elevated D-dimer (863.17 ± 39.06 ng/ml, p < 0.0001), CRP (24.31 ± 2.08 mg/L, p = 0.0055), and LDH (443.09 ± 43.88 U/L, p < 0.00001) levels compared to controls. RBS levels were also significantly elevated (p < 0.05). Gender had no strong independent effect on these biomarkers; however, CRP showed significant age-related differences in males (p < 0.05), while LDH demonstrated significant age-related elevation in both sexes (p < 0.001). Diabetic COVID-19 patients exhibited substantially higher glucose levels independent of gender. Conclusion: D-dimer, CRP, and LDH are valuable biomarkers for assessing disease severity in moderate-to-severe COVID-19, with LDH showing pronounced age-dependent elevation. These markers may serve as useful indicators for monitoring clinical progression and identifying high-risk patients, particularly among diabetic populations.